Feasibility of rapid discharge after transoral robotic surgery of the oropharynx. (16th June 2014) - Richmon, Jeremy D.; Feng, Allen L.; Yang, Wuyang; Starmer, Heather; Quon, Harry; Gourin, Christine G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate the use of an algorithm for rapid discharge after transoral robotic surgery (TORS) and its effect on postoperative complications. Study Design Retrospective cohort study. Methods A retrospective analysis of TORS cases from September 2009 to February 2013 was conducted. The effect of patient and tumor characteristics on postoperative length of stay (LOS) and complications were analyzed. Results A total of 91 patients were included; 79 underwent TORS for malignancy and 12 for a benign process. The mean LOS was 1.51 days (range, 1–5 days) with a median of 1 day. The mean time to initiation of oral diet was 1.26 days (range, 1–7 days) with a median of 1 day. Eleven (12%) patients experienced one or more complications during their postoperative course. Multivariate analysis demonstrated a significant association between patient and procedure variables and postoperative complications. TORS base of tongue reduction for obstructive sleep apnea (OSA) was associated with a significantly greater mean incremental time to initiation of oral diet (1.0 days, 95% confidence interval [CI]: 0.4 to 1.7, P < .001). A significantly greater mean incremental LOS was observed for patients with advanced comorbidity and a delay in initiation of oral diet beyond 24 hours. Conclusions Rapid initiation of oral diet and rapid discharge home is feasible and not associated with postoperative complications. Similarly, the performance of a concurrent neck dissection does not contribute to LOS or the development of postoperative complications. Patients undergoing TORS for OSA are at greater risk of delay in initiation of oral diet and increased LOS. Level of Evidence 4 Laryngoscope, 124:2518–2525, 2014